Benedict Cotruglio (Benko Kotruljević) - man on the border of two worlds and two epochs - Wróbel, Piotr (Balcanica Posnaniensia. Acta et studia, 2009)
The article presents the figure of Benedict Cotruglio (Benko Kotruljević, 1416–1469) – a merchant, diplomat, and humanist from Dubrovnik, author of The Book on the Art of Trade (1458), considered the first known work to describe the principles of double-entry bookkeeping. The study begins with an overview of the Republic of Dubrovnik in the 15th century, whose rapid economic development relied on maritime trade and diplomacy. Within this context, Cotruglio’s biography portrays him as a representative of the mercantile elite who lived and worked between two worlds – the conservative Balkans and the dynamic Mediterranean – as well as between the mentalities of the Middle Ages and the Renaissance. The aim of the research was to examine Cotruglio’s commercial, diplomatic, and literary activity in the broader framework of late medieval cultural and economic transformations. The author based his analysis on archival sources from Dubrovnik and Naples, as well as on editions and translations of Cotruglio’s works, particularly Il libro dell’arte di mercatura. The study applies textual criticism and interpretative methods rooted in economic and cultural history. The conclusions indicate that Cotruglio exemplifies a “man of two worlds,” combining the pragmatism of a merchant with the spirituality of a scholastic thinker and the Renaissance belief in the power of knowledge. His treatise not only introduced the fundamentals of modern accounting but also presented the moral ideal of a “perfect merchant,” who reconciles the pursuit of profit with piety and social responsibility. Cotruglio’s life and work illustrate the transition from the medieval to the Renaissance model of economic thought and ethics, making a valuable contribution to the study of early European commercial culture.